Mechanisms of immune evasion by head and neck cancer stem cells - Xavier, Flávia Caló Aquino; Silva, Jamerson Carvalho; Rodini, Camila Oliveira; Rodrigues, Maria Fernanda Setubal Destro (Frontiers in Oral Health, 2022)
Different mechanisms are involved in immune escape surveillance driven by Oral and Head and Neck Cancer Stem Cells (HNCSCs). The purpose of this review is to show the most current knowledge regarding the main impact of HNCSCs on tumor evasion through immunosuppression, CSCs phenotypes and environmental signals, highlighting strategies to overcome immune evasion. The main results drive the participation of cell surface receptors and secreted products and ligands, the crosstalk between cells, and genetic regulation. The reduction in CD8+ T cell recruitment and decreased effector of anti-PD-1 therapy by cells expressing BMI1 is a key event; Natural Killer cell ligands and cytokines needed for its activation and expansion are crucial to control tumor growth and to target CSCs by immunotherapy; CSCs expressing ALDH1 are related to increased expression of PD-L1, with a positive link between DNMT3b expression; CD276 expression in CSCs can act as a checkpoint inhibitor and together with Activator Protein 1 (AP-1) activation, they create continuous positive feedback that enables immune evasion by suppressing CD8+ T cells and prevent immune cell infiltration in head and neck cancer. These data demonstrate the relevance of the better understanding of the interaction between HNCSCs and immune cells in the tumor microenvironment. The ultimate clinical implication is to ground the choice of optimized targets and improve immune recognition for ongoing treatments as well as the response to approved immunotherapies.